Entwicklung der beruflichen Segregation von Männern und Frauen zwischen 1996 und 2005: eine Bestandsaufnahme auf betrieblicher Ebene - Miriam Beblo; Anja Heinze; Elke Wolf (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– Based on the Linked-Employer-Employee data from the IAB (LIAB) we show how the horizontal occupational segregation of men and women in German establishments developed between 1996 and 2005. For this purpose we apply the dissimilarity index and the standardized dissimilarity index at the establishment level. The analysis of the heterogeneity of firm-specific segregation is differentiated by region and sector. In spite of the small overall decrease in segregation over time, large differences between establishments are revealed. Both the female share and the share of part-time employees are considerably larger in less segregated establishments. The latter also tend to employ more highly educated workers and, in eastern Germany, a larger share of unskilled workers. A decomposition of the change in labour market segregation over time reveals that the small decrease in the dissimilarity index is mainly driven by an overall shift towards less segregated occupations. Based solely on the change in the gender ratio by occupation, the dissimilarity index in eastern Germany would even have increased.
Keywords: 330; Arbeitsmarktsegmentation; geschlechtsspezifischer Arbeitsmarkt; Segregation - Determinanten; Männerberufe; Frauenberufe; IAB-Linked-Employer-Employee-Datensatz; interner Arbeitsmarkt; regionaler Vergleich; Wirtschaftszweige; Beschäftigtenstruktur; Geschlechterverteilung; Qualifikationsstruktur; Teilzeitarbeitnehmer; Berufsstrukturwandel; Berufsgruppe; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland